Poison flower : a Jane Whitefield novel - Perry, Thomas, 1947- (Perry, Thomas, 1947- Jane Whitefield novel (Tantor Media), 2012)
Protecting a man wrongly charged with the murder of his wife, Jane Whitefield is shot and abducted by the real culprits, who threaten to kill her if she does not reveal her client's whereabouts.